Genome-Wide Analysis of GmMYB S20 Transcription Factors Reveals Their Critical Role in Soybean Nodulation - Junchen Leng; Ruobing Xu; Yanshuang Liu; Tianshu Jiang; Haiying Hu; Zhaojun Ding; Shaojun Dai (Plants, 2025)
Soybean relies on symbiotic nitrogen fixation (SNF) to support sustainable agriculture. In this study, we conducted a comprehensive analysis of the GmMYB transcription factor subfamily 20, with a focus on GmMYB62a and GmMYB62b. Phylogenetic and structural analyses revealed that these genes are evolutionarily conserved among legumes and possess distinct domain architectures. Expression profiling and GUS staining showed that GmMYB62a and GmMYB62b are constitutively expressed in nodules. Functional analyses revealed that loss of GmMYB62s function significantly reduced nodule density, while overexpression promoted nodulation. Transcriptomic analysis (RNA-seq) further demonstrated that GmMYB62s regulate key pathways, including hormone signaling, immune responses, and cell wall metabolism, thereby coordinating symbiotic interactions. Collectively, our findings identify GmMYB62a and GmMYB62b as critical molecular regulators of nodulation in soybean, providing promising targets for improving symbiotic nitrogen fixation efficiency in legume crops.